The Regulatory Protein ChuP Connects Heme and Siderophore-Mediated Iron Acquisition Systems Required for Chromobacterium violaceum Virulence - de Lima, Vinicius M.; Batista, Bianca B.; da Silva Neto, José F. (Frontiers in Cellular and Infection Microbiology, 2022)
Chromobacterium violaceum is an environmental Gram-negative beta-proteobacterium that causes systemic infections in humans. C. violaceum uses siderophore-based iron acquisition systems to overcome the host-imposed iron limitation, but its capacity to use other iron sources is unknown. In this work, we characterized ChuPRSTUV as a heme utilization system employed by C. violaceum to explore an important iron reservoir in mammalian hosts, free heme and hemoproteins. We demonstrate that the chuPRSTUV genes comprise a Fur-repressed operon that is expressed under iron limitation. The chu operon potentially encodes a small regulatory protein (ChuP), an outer membrane TonB-dependent receptor (ChuR), a heme degradation enzyme (ChuS), and an inner membrane ABC transporter (ChuTUV). Our nutrition growth experiments using C. violaceum chu deletion mutants revealed that, with the exception of chuS, all genes of the chu operon are required for heme and hemoglobin utilization in C. violaceum. The mutant strains without chuP displayed increased siderophore halos on CAS plate assays. Significantly, we demonstrate that ChuP connects heme and siderophore utilization by acting as a positive regulator of chuR and vbuA, which encode the TonB-dependent receptors for the uptake of heme (ChuR) and the siderophore viobactin (VbuA). Our data favor a model of ChuP as a heme-binding post-transcriptional regulator. Moreover, our virulence data in a mice model of acute infection demonstrate that C. violaceum uses both heme and siderophore for iron acquisition during infection, with a preference for siderophores over the Chu heme utilization system.